Study of GPS derived Total Electron Content and Scintillation Index variations over Indian Arctic and Antarctic stations (Journal of Scientific Research, 2013)
In the present study we have investigated the monthly and seasonal variability of total electron content (TEC) and amplitude scintillation index (S4) over two Indian polar stations Maitri (Antarctic) and Ny-Alesund (Arctic), during the low solar activity period 2008. We have used the Novatels dual frequency GPS receiver GSV4004A to accomplish this study. From our analysis we observed that TEC achieves its highest values during the months of November and December while during the month of May and June the lowest values of TEC were recorded at Maitri station. Similarly during summer season the highest values of TEC are recorded while in winter season lowest values of TEC are observed. The scintillations that occurred during the year 2008 at Maitri as well as at Ny-Alesund were generally found to be of weak type (S4?0.1), although few cases of moderate (S4?0.3) and strong (S4?0.5) scintillation were also observed. The occurrence characteristics of scintillations showed that maximum scintillations at Maitri occur during the month of July and August while least scintillations occur during the month of January and February. This type of ionospheric variability can be explained on the basis of solar irradiance at Polar Regions.Keywords: Total electron content; Scintillation index; Polar ionosphere.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.12724        J. Sci. Res. 5 (2), 255-264 (2013)